Miniaturization and Biocompatible Encapsulation for Implantable Biomedical Silicon Devices. (1st January 2015) - Souriau, J-C.; Morales, J. M. Herrera; Castagné, L.; Simon, G.; Amara, K.; Boutaud, B.
Abstract : This paper presents a new strategy of packaging developed for medical applications which includes a sensor and an integrated circuit inside a hermetic silicon box that could be embedded in a cardiac lead in order to monitor the endocardial acceleration. The electronic components are placed on a silicon interposer wafer which was bonded by the eutectic AuSi with a silicon wafer lid containing cavities. Different metal stacks of the sealing ring including a barrier and Au have been studied. The gas content and hermeticity of the package were analyzed using Residual Gas Analysis (RGA) and biodegradation were tested in saline solution. The final silicon package was encapsulated with biocompatible materials that have high conformality deposition and act as good bi-directional barrier. Materials behavior that had been reported in literature as biocompatible and compatible with fabrication in standard clean rooms were studied. Finally, packaging materials were tested in cytotoxicity.